(untitled) (Research, Society and Development, 2021)
Brazil generates substantial quantity of poultry litter waste because of its worldwide prominence in the production of broiler chickens. The volume of the poultry litter biomass generates considerable environmental impact. The objective was to characterize the biochar produced from poultry litter residue under different conditions with the aim of determining the best residence time and temperature. Poultry litter was collected after two batches of chicken breeding. Five treatments for biochar production were carried out at a temperature of 450 °C (defined by thermogravimetric analysis - TGA) and residence times of 0.5, 1, 2, 4, and 6h. The biochar produced was assessed using proximate analysis, moisture content, gravimetric yield, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and HHV (higher heating value). The results revealed that the best conditions for biochar production was 450 °C (pyrolysis) and residence time of 0.5h, with 37.21% gravimetric yield. We concluded that the biochar produced in this study is recommended for soil application but was not suitable for energy purposes because of its high ash content (up to 33.66%) and low HHV (18,907 J g-1).